High rate of HLA class II mRNA synthesis in rheumatoid arthritis joints and its persistence in culture: down-regulation by recombinant interleukin 2. - Kissonerghis, A; Maini, R; Feldmann, M (1989)
The expression of HLA class II mRNA was investigated in the joints of patients with active rheumatoid arthritis (RA) in order to evaluate patterns of synthesis. Northern hybridization analysis showed that HLA class II gene transcripts in RA joints were of the correct sizes, and subsequent analyses were performed by slot blotting. All active RA samples expressed high levels of HLA-DR, DP, and DQ mRNA with DP and DQ less than DR. Synovial fluid or membrane cells, chiefly a mixture of T cells and macrophages, were placed in culture, in the absence of any stimulation. The levels of mRNA remained at a high level in vitro. The half of HLA-DR mRNA in joint cells was very brief (approximately 30 min), indicating that prolonged synthesis was due to restimulation of the cells. The effect of lymphokines on HLA class II regulation on joint cell was assessed. Gamma interferon was capable of augmenting HLA-DR to some extent, but paradoxically interleukin 2 at concentrations optimal for stimulating T cells, diminished HLA-DR expression.